Iron monatomic catalyst as well as preparation method and application thereof

By using porous gaminoximated polyacrylonitrile as a pyrolysis precursor in catalyst preparation, the Fe-N2O2 single atomic active site was formed, and the problem of poor activity and stability of iron single atomic catalyst was solved, and efficient catalysis and low-cost large-scale production were achieved.

CN119601680AActive Publication Date: 2025-03-11TIANJIN POLYTECHNIC UNIV

Patent Information

Application Number
CN202411831757.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The activity and stability of existing iron single atom catalysts are poor, and their preparation process is high, making it difficult to achieve large-scale commercialization.

Method used

Iron single atomic catalyst with high specific surface area and rich three-dimensional continuous gradation porous structure was prepared by reacting polyacrylonitrile with hydroxylamine and metal salt to form porous amidoximetyl polyacrylonitrile (APAN), and then forming Fe-N2O2 single atomic active sites during the pyrolysis process.

Benefits of technology

The ORR in the catalyst's efficient catalytic fuel cell and metal-air battery is achieved, with high catalytic activity and stability, and reduces the cost of raw materials, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601680A_ABST
    Figure CN119601680A_ABST
Patent Text Reader

Abstract

The invention discloses an iron monatomic catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalyst preparation. Porous amidoximation polyacrylonitrile is prepared from polyacrylonitrile powder by combining gelation, a non-solvent phase separation process and an amidoximation reaction, then the porous amidoximation polyacrylonitrile is soaked in a metal salt solution to obtain porous amidoximation polyacrylonitrile chelated with iron ions and zinc ions, and finally the high-temperature pyrolysis process is performed. The porous metal chelate precursor is converted to a porous iron monatomic catalyst. The prepared catalyst has high specific surface area and abundant three-dimensional continuous hierarchical porous structures, contains abundant Fe-N2O2 catalytic active sites, and can efficiently catalyze cathode oxygen reduction reaction in fuel cells and metal-air cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to an iron single atom catalyst and a preparation method and application thereof. Background Art

[0002] Fuel cells and metal-air batteries are a type of clean energy technology that can efficiently convert chemical energy into electrical energy. They show great application potential in many fields such as transportation power supply, stationary power generation systems, and portable power devices. In the working principle of fuel cells and metal-air batteries, an oxidation reaction of fuel or metal occurs at the anode, and an oxygen reduction reaction (ORR) occurs at the cathode. Compared with the anode reaction, the kinetics of cathode ORR are slow, and catalysts are usually required to accelerate the reaction kinetics. For a long time, platinum-based catalysts have dominated due to their high ORR catalytic performance. However, platinum is a precious metal, and its high cost and resource scarcity have become the main bottlenecks restricting the large-scale commercialization of these technologies. Therefore, it is urgent to develop non-precious metal ORR catalysts with high catalytic activity.

[0003] Currently, many studies focus on the preparation of iron single-atom catalysts by pyrolysis of metal-organic frameworks (MOFs). Although MOFs offer significant advantages in the preparation of single-atom catalysts, this technical path is also accompanied by a series of challenges. The primary challenge is the thermal stability of MOFs during high-temperature pyrolysis, which may lead to the destruction of the material structure and the collapse of the pore structure, thus negatively affecting the performance of the catalyst. Secondly, single-atom catalysts derived from MOFs usually have smaller pore sizes, which may increase mass transfer resistance and limit the efficiency of the catalytic reaction. In addition, the synthesis process of MOFs is not only technically demanding but also costly, which may become an obstacle to its application on an industrial scale. Another key issue is that the loading amount of monodispersed iron in the iron single-atom catalyst obtained by pyrolysis of MOFs is usually low (generally less than 1wt.%), which limits the number of iron single-atom active sites in the catalyst, thereby affecting the overall performance of the catalyst. Therefore, developing iron single-atom catalysts with hierarchical porous structures with high specific surface area, increasing the iron loading while maintaining the high dispersion of iron species, and achieving low-cost large-scale production is one of the key challenges in realizing commercially valuable iron single-atom catalysts. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an iron single atom catalyst and a preparation method and application thereof, so as to solve the technical problem of poor catalyst activity and stability.

[0005] To achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing an iron single atom catalyst, comprising the following steps:

[0006] S1, dissolving polyacrylonitrile in an organic solvent to obtain a uniform polyacrylonitrile organic solution, and then allowing the polyacrylonitrile organic solution to stand for 2-24 hours, and as the temperature of the solution decreases and the organic solvent partially evaporates, the polyacrylonitrile organic solution gradually gels to form a polyacrylonitrile organic gel;

[0007] S2, placing the polyacrylonitrile organogel in a hydroxylamine aqueous solution, soaking it at 3-5°C for 2-72 hours, then placing it in a metal salt solution, soaking it at room temperature for 6-72 hours, and finally rinsing and drying it to obtain an intermediate;

[0008] Since polyacrylonitrile is poorly soluble in water, the polyacrylonitrile organogel undergoes a non-solvent-induced phase separation process in water to form a polymer-rich phase and a solvent-rich phase. The separation process of polyacrylonitrile and the organic solvent leads to the formation of polyacrylonitrile with a porous structure. At the same time, a nucleophilic addition reaction occurs between polyacrylonitrile and hydroxylamine, converting the cyano group into an amidoxime group, thereby generating porous amidoximated polyacrylonitrile (APAN). Porous amidoximated polyacrylonitrile contains abundant amidoxime groups, which have good chelating ability for many metal ions, providing abundant anchoring sites for the introduction of iron ions and zinc ions.

[0009] Immersing APAN in a mixed metal salt solution containing iron and zinc ions can achieve efficient chemical adsorption of these two metal ions. Both iron and zinc ions form chelates containing FeN2O2 and ZnN2O2 coordination structures with the amidoxime groups in porous amidoxime polyacrylonitrile. The main function of the Zn-N2O2 coordination structure is to dilute the Fe-N2O2 coordination structure and prevent the aggregation of iron species during the pyrolysis process. In addition, zinc has a low boiling point and can be completely evaporated in the subsequent pyrolysis, ensuring that the Fe-N2O2 coordination structure can be converted into isolated Fe-N2O2 single-atom active sites. Compared with simple physical mixing, the formation of amidoxime metal chelates ensures the uniform distribution of iron and zinc ions in the precursor, and at the same time forms clear Fe-N2O2 and Zn-N2O2 coordination structures, providing an ideal precursor for the preparation of single-atom catalysts with Fe-N2O2 sites.

[0010] S3. The intermediate is placed in a protective atmosphere, heat treated at 200-300°C for 1-3h to stabilize the pore structure, and then heated to 600-1200°C for pyrolysis for 2-8h to obtain an iron single atom catalyst containing FeN2O2 sites.

[0011] On the basis of the above technical solution, the present invention can also be improved as follows:

[0012] Furthermore, the organic solvent is N,N-dimethylformamide or disulfide.

[0013] Furthermore, the concentration of the polyacrylonitrile organic solution is 50-500 g / L.

[0014] Furthermore, the concentration of the hydroxylamine aqueous solution is 0.02-2 mol / L.

[0015] Furthermore, the metal salt solution is a mixed solution of iron salt and zinc salt, wherein the total concentration of metal ions is 0.02-2 mol / L, and the molar ratio of the iron ion concentration to the total metal ion concentration is 0.001-0.5:1.

[0016] Furthermore, the iron salt is iron nitrate, iron chloride or iron sulfate, and the zinc salt is zinc nitrate, zinc chloride or zinc sulfate.

[0017] Furthermore, the drying temperature is 40-80°C and the drying time is 1-4h.

[0018] Furthermore, the protective atmosphere is made of nitrogen, argon or helium.

[0019] Furthermore, the pyrolysis is divided into two stages, specifically: first pyrolysis at 950-1200°C for 1-4h, and then pyrolysis at 600-1200°C for 1-4h.

[0020] During the pyrolysis process, the aggregation tendency of iron species is suppressed by the introduction of zinc species, which effectively avoids the aggregation of iron species and helps to form single atomic sites. When the first pyrolysis is carried out at a temperature above 950°C, the Fe-N2O2 coordination structure is converted into Fe-N2O2 single atomic active sites, and the Zn-N2O2 coordination structure undergoes a carbon thermal reduction reaction to be converted into elemental zinc, which is then completely evaporated at high temperature. The secondary pyrolysis can increase the specific surface area of ​​the material, thereby increasing the number of Fe-N2O2 single atomic sites in the catalyst, thereby enhancing the activity of the catalyst.

[0021] The invention also discloses an iron single-atom catalyst prepared by the preparation method.

[0022] The invention also discloses the application of the iron single-atom catalyst in the preparation of battery electrodes.

[0023] The beneficial effects of the present invention are:

[0024] 1. The present invention prepares an iron single-atom catalyst containing FeN2O2 sites by thermally decomposing porous amidoximated polyacrylonitrile chelated with iron ions and zinc ions. The single-atom catalyst has a high specific surface area and a rich three-dimensional continuous hierarchical porous structure, contains a large number of Fe-N2O2 catalytic active sites, and can efficiently catalyze the cathode reaction ORR in fuel cells and metal-air batteries. The single-atom catalyst prepared by the method of the present invention was tested, and the iron loading was measured by inductively coupled plasma mass spectrometry to be up to

[0025] The rotating disk electrode test found that its half-wave potential can reach 0.92V and 0.79V in alkaline and acidic electrolytes respectively, and it still maintains high activity after accelerated stress testing, so it has high catalytic activity and stability.

[0026] 2. The raw materials used in the present invention are economical, the process steps are simple, suitable for large-scale production, and have high industrial application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Fe3NOC-900, Fe3NOC, NOC-900 and Fe 100 Scanning electron microscope photo of NOC-900;

[0028] Figure 2 Fe3NOC-900, Fe3NOC, NOC-900 and Fe 100 Transmission electron microscope photo of NOC-900;

[0029] Figure 3 X-ray near-edge absorption structure (XANES) spectra of Fe3NOC-900 and Fe3NOC;

[0030] Figure 4 The extended edge absorption structure (EXAFS) spectra of Fe3NOC-900 and Fe3NOC;

[0031] Figure 5 Nitrogen isothermal adsorption-desorption curves of Fe3NOC-900 and Fe3NOC;

[0032] Figure 6 Fe3NOC-900, Fe3NOC, NOC-900 and Fe 100 ORR polarization curve of NOC-900 in alkaline electrolyte;

[0033] Figure 7 Fe3NOC-900, Fe3NOC, NOC-900 and Fe 100 ORR polarization curve of NOC-900 in acidic electrolyte;

[0034] Figure 8 ORR polarization curves of Fe3NOC-900 before and after stability test in alkaline electrolyte;

[0035] Fig. 9 ORR polarization curve of Fe3NOC-900 before and after stability test in acidic electrolyte. DETAILED DESCRIPTION

[0036] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

[0037] Example 1

[0038] A method for preparing an iron single-atom catalyst comprises the following steps:

[0039] S1. Dissolve 0.5 g of polyacrylonitrile (PAN) in 2.5 mL of N,N-dimethylformamide (DMF) to obtain a polyacrylonitrile organic solution. Then pour the polyacrylonitrile organic solution into a container with a size of 60×20×2 mm. 3 The polyacrylonitrile organic gel was obtained by placing the polyacrylonitrile organic gel in a rectangular polytetrafluoroethylene mold and leaving it at room temperature for 2 hours.

[0040] S2, placing the polyacrylonitrile organogel in a 0.02 mol / L hydroxylamine aqueous solution, soaking it at 3°C ​​for 72 h to generate porous amidoxime polyacrylonitrile (APAN), then placing APAN in a mixed aqueous solution of 6 mmol / L ferric chloride and 194 mmol / L zinc chloride, soaking it at room temperature for 6 h, finally rinsing it with deionized water, and drying it in an oven at 40°C for 4 h to obtain the intermediate (Fe3Zn 97 -APAN);

[0041] S3. The intermediate is placed in an argon-filled atmosphere, heat treated at 200°C for 3 hours, then heated to 950°C for a first pyrolysis for 4 hours, and then the temperature is adjusted to 600°C and pyrolyzed for a second time for 1 hour to obtain an iron single-atom catalyst (Fe3NOC-600) containing FeN2O2 sites.

[0042] Example 2

[0043] A method for preparing an iron single-atom catalyst comprises the following steps:

[0044] S1. Dissolve 0.5 g of polyacrylonitrile (PAN) in 2.5 mL of disulfide sulfoxide (DMSO) to obtain a polyacrylonitrile organic solution, and then pour the polyacrylonitrile organic solution into a container with a size of 60×20×2 mm. 3 The polyacrylonitrile organic gel was obtained by placing the polyacrylonitrile organic gel in a rectangular polytetrafluoroethylene mold and leaving it at room temperature for 24 hours.

[0045] S2, placing the polyacrylonitrile organogel in a 2 mol / L hydroxylamine aqueous solution, soaking it at 5°C for 2 h, generating porous amidoxime polyacrylonitrile (APAN), then placing the APAN in a mixed aqueous solution of 6 mmol / L ferric sulfate and 194 mmol / L zinc sulfate, soaking it at room temperature for 48 h, finally rinsing it with deionized water, and drying it in an oven at 80°C for 1 h, obtaining the intermediate (Fe3Zn 97 -APAN);

[0046] S3. The intermediate is placed in a helium-filled atmosphere, heat treated at 300°C for 2 hours, then heated to 1200°C for a first pyrolysis for 2.5 hours, and then the temperature is adjusted to 1200°C for a second pyrolysis for 4 hours to obtain an iron single-atom catalyst (Fe3NOC-1200) containing FeN2O2 sites.

[0047] Example 3

[0048] A method for preparing an iron single-atom catalyst comprises the following steps:

[0049] S1. Dissolve 0.5 g of polyacrylonitrile (PAN) in 2.5 mL of N,N-dimethylformamide (DMF) to obtain a polyacrylonitrile organic solution. Then pour the polyacrylonitrile organic solution into a container with a size of 60×20×2 mm. 3 The polyacrylonitrile organic gel was obtained by placing the polyacrylonitrile organic gel in a rectangular polytetrafluoroethylene mold and leaving it at room temperature for 3 hours.

[0050] S2, placing the polyacrylonitrile organogel in a 0.2 mol / L hydroxylamine aqueous solution, soaking it at 4°C for 72 h to generate porous amidoxime polyacrylonitrile (APAN), then placing the APAN in a mixed aqueous solution of 6 mmol / L ferric nitrate and 194 mmol / L zinc nitrate, soaking it at room temperature for 48 h, and finally rinsing it with deionized water, drying it in an oven at 60°C for 2.5 h, and obtaining the intermediate (Fe3Zn 97 -APAN);

[0051] S3. The intermediate was placed in a nitrogen-filled atmosphere, heat treated at 270°C for 1 h, then heated to 1000°C for a first pyrolysis for 2.5 h, and then the temperature was adjusted to 900°C for a second pyrolysis for 2.5 h to obtain an iron single-atom catalyst (Fe3NOC-900) containing FeN2O2 sites.

[0052] Comparative Example 1

[0053] The difference between this comparative example and Example 3 is that the secondary pyrolysis treatment in step S3 is omitted, and the remaining implementation conditions are the same as those in Example 3 to obtain a Fe3NOC catalyst.

[0054] Comparative Example 2

[0055] The difference between this comparative example and Example 3 is that the metal salt solution in step S2 is replaced by a mixed solution of 6 mmol / L ferric nitrate and 194 mmol / L zinc nitrate with a zinc nitrate solution with a concentration of 200 mmol / L, and the other implementation conditions are the same as those in Example 3, thereby obtaining a nitrogen / oxygen co-doped carbon catalyst (NOC-900) that does not contain Fe.

[0056] Comparative Example 3

[0057] The difference between this comparative example and Example 3 is that the metal salt solution in step S2 is replaced by a mixed solution of 6 mmol / L ferric nitrate and 194 mmol / L zinc nitrate with a 200 mmol / L ferric nitrate solution, and the other implementation conditions are the same as those in Example 3 to obtain a nitrogen / oxygen co-doped carbon catalyst (Fe) containing Fe particles. 100 NOC-900).

[0058] The samples used in the following experiments are the ORR catalysts prepared in Example 3 and Comparative Examples 1-3.

[0059] Experimental Example 1 Structural Characterization

[0060] Example 3 (Fe3NOC-900), Comparative Example 1 (Fe3NOC), Comparative Example 2 (NOC-900) and Comparative Example 3 (Fe 100 The scanning electron microscopy (SEM) of the catalyst prepared by NOC-900 is as follows Figure 1 As shown. It can be seen that Fe3NOC-900, Fe3NOC-900, NOC-900 and Fe 100 NOC-900 all present a similar three-dimensional continuous open pore structure with a pore size of 100-300 nm, which belongs to the category of macroscopic macropores, indicating that porous APAN is a favorable precursor for the preparation of porous carbon-based materials.

[0061] Fe3NOC-900, Fe3NOC, NOC-900 and Fe 100Transmission electron microscopy (TEM) of NOC-900 Figure 2 As shown in the figure, it can be seen that Fe3NOC and Fe3NOC-900 and NOC-900 without Fe all present a lamellar structure, and no metal particles can be observed. 100 The presence of a large number of metal particles in NOC-900 indicates that the appropriate introduction of Zn in the precursor can effectively prevent the aggregation of Fe species to form particles during pyrolysis, thereby ensuring that Fe exists in a highly dispersed single atomic form.

[0062] The X-ray near-edge absorption structure (XANES) spectra of Fe3NOC-900 and Fe3NOC are shown in Figure 2. Figure 3 As shown in the figure, compared with the reference samples (iron foil, chlorinated iron phthalocyanine), the Fe oxidation state in Fe3NOC-900 and Fe3NOC is similar to that in chlorinated iron phthalocyanine, both close to +3. This result shows that Fe3NOC-900 and Fe3NOC do not contain iron particles, because the oxidation state of elemental iron in iron foil is 0. The extended edge absorption structure (EXAFS) spectra of Fe3NOC-900 and Fe3NOC are shown in Figure 1. Figure 4 As shown in the figure, Fe3NOC-900 and Fe3NOC have no peak at the Fe-Fe distance, only There are peaks within a distance of , which indicates that there is only Fe-N / O coordination structure in the sample, that is, all Fe species are distributed in single atoms. These phenomena indicate that secondary pyrolysis does not cause agglomeration of Fe species. In summary, the method of the present invention can successfully prepare Fe single atom catalysts.

[0063] The nitrogen isothermal adsorption and desorption curves of Fe3NOC-900 and Fe3NOC are as follows: Figure 5 Fe3NOC-900 and Fe3NOC show typical IV type adsorption-desorption curves with an obvious hysteresis loop in the P / P0 range of 0.42-0.95, which indicates that both have microporous / mesoporous structures, but the BET specific surface area of ​​Fe3NOC is 236m 2 / g, the BET specific surface area of ​​Fe3NOC-900 is 483m 2 Although Fe3NOC-900 and Fe3NOC have similar Fe single atom sites, secondary pyrolysis can increase the specific surface area of ​​the material, indicating that the present invention can successfully prepare a hierarchical pore Fe single atom catalyst with a large specific surface area and rich macropores, micropores and mesopores.

[0064] The Fe3NOC-900 prepared in Example 3 was tested by inductively coupled plasma mass spectrometry, and the iron loading in the catalyst was finally measured to be 1.5 wt.%.

[0065] Experimental Example 2 Electrochemical Performance Test

[0066] Weigh 10 mg of catalyst samples (Fe3NOC-900, Fe3NOC, NOC-900 and Fe 100 NOC-900), fully dispersed with 950 μL of water and 50 μL of Nafion (5 wt%) mixed solution, and then 12 μL of the suspension was dripped onto the glassy carbon electrode (electrode area 0.196 cm 2 ) on the electrode surface, after the electrode surface was completely dried, the ORR polarization curves were collected in O2-saturated 0.1M KOH or HClO4 solution using a rotating disk test technique, with an electrode speed of 1600rpm, a potential range of 0.05-1.1V vs RHE, and a scan rate of 10mV / s. The catalyst stability was tested using accelerated stress tests (ASTs), with 10,000 cyclic voltammetry scans of the electrode in 0.1M KOH or HClO4 solution at a scan rate of 100mV / s, with a potential range of 0.6-1.0V vs RHE.

[0067] Fe3NOC-900, Fe3NOC, NOC-900 and Fe 100 The ORR polarization curve of NOC-900 is shown in Figure 6 and Figure 7 As shown in Figure 2, it can be seen that in the alkaline electrolyte (0.1M KOH), the Fe 100 The ORR catalytic performance of NOC-900 is better than that of NOC-900 without Fe, but lower than that of Fe single-atom catalysts Fe3NOC and Fe3NOC-900, where the half-wave potential of Fe3NOC-900 reaches 0.92 V. In acidic electrolyte (0.1 M HClO4), NOC-900 without Fe has almost no ORR activity, while Fe containing Fe particles has a 100 The ORR catalytic activity of NOC-900 is poor, while the activity of Fe single-atom catalysts Fe3NOC and Fe3NOC-900 is relatively high, among which the half-wave potential of Fe3NOC-900 can reach 0.79V. However, whether in alkaline or acidic electrolytes, the catalytic activity of Fe3NOC-900 is better than that of Fe3NOC, indicating that secondary pyrolysis can enhance the activity of Fe single-atom catalysts. The above shows that the Fe single-atom catalyst prepared by the present invention has high activity in both alkaline and acidic electrolytes.

[0068] The ORR polarization curves of Fe3NOC-900 before and after the stability test in acidic and alkaline environments are shown in Figure 2. Figure 8 and Fig. 9As shown. It can be seen that the half-wave potential of Fe3NOC-900 in alkaline electrolyte (0.1M KOH) decreased by 20mV after ASTs; the half-wave potential of Fe3NOC-900 in acidic electrolyte (0.1M HClO4) decreased by 16mV after ASTs. The above shows that the Fe single atom catalyst prepared by the present invention has high stability in both alkaline and acidic electrolytes.

[0069] In summary, the present invention utilizes porous amidoxime polyacrylonitrile to simultaneously chelate iron ions and zinc ions as pyrolysis precursors, which can effectively avoid the aggregation of iron species during the pyrolysis process, thereby preparing an Fe single-atom catalyst with a rich hierarchical porous structure and a large specific surface area. The prepared Fe single-atom catalyst has high activity and stability in catalyzing ORR.

Claims

1. A method for preparing an iron single-atom catalyst, characterized in that: The following steps are involved: S1, dissolving polyacrylonitrile in an organic solvent, and then standing for 2-24 hours to obtain a polyacrylonitrile organogel; S2, placing the polyacrylonitrile organogel in a hydroxylamine aqueous solution, soaking it at 3-5°C for 2-72 hours, then placing it in a metal salt solution, soaking it at room temperature for 6-72 hours, and finally rinsing and drying it to obtain an intermediate; S3. Place the intermediate in a protective atmosphere, heat treat at 200-300° C. for 1-3 h, then heat to 600-1200° C. for pyrolysis for 2-8 h to obtain an iron single atom catalyst.

2. The method for preparing the iron single atom catalyst according to claim 1, characterized in that: The organic solvent is N,N-dimethylformamide or disulfide.

3. The method for preparing the iron single atom catalyst according to claim 1, characterized in that: The concentration of the hydroxylamine aqueous solution is 0.02-2 mol / L.

4. The method for preparing the iron single atom catalyst according to claim 1, characterized in that: The metal salt solution is a mixed solution of iron salt and zinc salt, wherein the total concentration of metal ions is 0.02-2 mol / L, and the molar ratio of the iron ion concentration to the total metal ion concentration is 0.001-0.5:

1.

5. The method for preparing the iron single atom catalyst according to claim 4, characterized in that: The iron salt is iron nitrate, iron chloride or iron sulfate, and the zinc salt is zinc nitrate, zinc chloride or zinc sulfate.

6. The method for preparing the iron single atom catalyst according to claim 1, characterized in that: The drying temperature is 40-80° C. and the drying time is 1-4 hours.

7. The method for preparing the iron single atom catalyst according to claim 1, characterized in that: The protective atmosphere is nitrogen, argon or helium.

8. The method for preparing the iron single atom catalyst according to claim 1, characterized in that: The pyrolysis is divided into two stages, specifically: first pyrolysis at 950-1200° C. for 1-4 h, and then pyrolysis at 600-1200° C. for 1-4 h.

9. An iron single atom catalyst, characterized in that The method is prepared by the method according to any one of claims 1 to 8.

10. Use of the iron single atom catalyst according to claim 9 in the preparation of battery electrodes.

Citation Information

Patent Citations

  • Amidoxime-modified polyacrylonitrile nanofiber membrane bimetallic complex catalyst and preparation method thereof

    CN103551195A

  • Water-soluble amidoximation polyacrylonitrile solution and preparation method thereof

    CN108530566A

  • Element-doped three-dimensional porous carbon material andas well as preparation method and application thereof

    CN109019559A

  • High-phosphorus-nitrogen co-doped three-dimensional porous carbon block and preparation method and application thereof

    CN111362251A

  • Self-supporting M-N / C oxygen reduction catalyst and preparation method and application thereof

    CN113206260A

Cited By

  • Porous transition metal-nitrogen-carbon catalyst as well as preparation method and application thereof

    CN120149434A